Analisis Prediksi Kebangkrutan Perusahaan Asuransi Kerugian Di Indonesia - Erizal Erizal; Margaretha Michella Gunawan; M. Nasyubun (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The application of the bankruptcy model using the Altman Z-score model is carried out to predict financial difficulties by using balance sheet analysis which can reflect the company's financial performance. Insurance companies are needed to minimize risks and uncertainties for futureprotection. Altman's Z-score model is analyzed through the calculation results if it is smaller than <1.1 it is concluded that the company is at high risk, if the calculation results are 1.1-2.6 it is concluded that the company is prone to bankruptcy, and if the calculation result is> 2.6 itcan be said that the company is healthy. So that the probability of bankruptcy can be estimated using the Z- score Altman method. This modeling can be used by insurance companies in making decisions. (MMG) Keywords: Bankruptcy, Financial Performance, Altman's Z-score Method